2007
DOI: 10.1080/00102200600637584
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plug and Corona Abilities to Ignite Stoichiometric and Lean Methane/Air Mixtures

Abstract: In this work, spark plug and corona discharge of 3-20 ms in duration have been used for ignition of stoichiometric and lean fuel methane= air mixtures. Comparison of spark plug and corona ignition abilities shows that corona discharge allows more efficient ignition with less discharge energy. It is proved experimentally that corona ignition provides faster combustion due to larger discharge volume, generation of turbulence around the discharge electrodes promoting combustion and assistance to the flame front p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In commercial ignition devices, all these problems are solved by supplying much more energy than should be needed in a theoretical combustion ignition model. However, alternative solutions using non-thermal plasmas for car engine applications are starting to emerge [3][4][5][6][7][8][9]. Ten years ago, not many scientific works were conducted on these kinds of ignition systems because of strong technological issues but also because experimental studies on multiscale physical and chemical processes under severe conditions of temperature, pressure and aerodynamics are very difficult to carry out.…”
Section: Introductionmentioning
confidence: 99%
“…In commercial ignition devices, all these problems are solved by supplying much more energy than should be needed in a theoretical combustion ignition model. However, alternative solutions using non-thermal plasmas for car engine applications are starting to emerge [3][4][5][6][7][8][9]. Ten years ago, not many scientific works were conducted on these kinds of ignition systems because of strong technological issues but also because experimental studies on multiscale physical and chemical processes under severe conditions of temperature, pressure and aerodynamics are very difficult to carry out.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that besides spark discharges, conventionally used for ignition, other plasma sources may be effective, including those producing non-thermal plasma. In particular, interesting experimental results have been obtained on initiation of combustion of cold methane-air and propaneair mixtures by transient plasma (or pulsed corona) discharges [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem and achieve successful ignition in lean fuel/air mixture, especially in ICEs, a reliable ignition strategy, that is, nonequilibrium plasma-assisted ignition/combustion (PAI/PAC) technology is proposed (Bellenoue et al, 2007;Cathey et al, 2007;Cathey et al, 2008;Singleton et al, 2010;Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The novel promising ignition systems characterized by nonequilibrium plasma can be created by corona discharge (Bellenoue et al, 2007), nanosecond repetitively pulsed discharge (NRPD) (Cathey et al, 2007), and gliding arc discharge (Zhu et al, 2017). Among them, NRPD is the one with a smaller proportion of energy thermalization which has been demonstrated great potential to achieve stable combustion in lean-burn gasoline engines (Cathey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%